(rev.) Дмитрий Фурман, Движение по спирали. Политическая система России в ряду других систем, Москва 2010, pp. 168 [Dmitrij Furman, The Movement of the Spiral. The Political System of Russia among Other Systems, “Ves Mir” Publishing House, Moskwa 2010] - Prokop, Maryana (The Copernicus Journal of Political Studies, 2018)
Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14760